The effects of alpha-lipoic acid (ALA) on the urinary bladder injury in rats exposed to chronic stress: a histochemical study - ŞİRVANCI, SERAP (My University, 2022)
Objective: In the present study, we aimed to investigate the morphological and biochemical effects of alpha-lipoic acid (ALA) on bladder injury caused by water avoidance stress (WAS) and to show its effect on the number of degranulated mast cells, which increase after stress.Materials and Methods: Wistar albino rats were subjected to WAS and the animals in the treatment group were injected ALA. After the urinary bladder tissues were subjected to routine tissue processing, hematoxylin-eosin staining and periodic acid-Schiff reaction were applied to observe general morphology and acidic toluidine blue method to investigate mast cells. Biochemical assessments of malondialdehyde (MDA) and glutathione (GSH) were also obtained. Transmission electron microscope was used for the ultrastructural, and scanning electron microscope for the topographical analyses. Results: The experiments showed that chronic stress caused injury in the bladder, increased degranulated and total number of mast cells and decreased GSH and increased MDA levels. ALA treatment after WAS ameliorated bladder injury in most areas, decreased degranulated and total mast cell number and increased GSH and decreased MDA levels.Conclusion: It was concluded that ALA can be a useful agent in the treatment of interstitial cystitis.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; Alpha-lipoic acid (ALA); Interstitial cystitis; Mast cell; Stress; Urinary bladder; MAST-CELL DEGRANULATION; INTERSTITIAL CYSTITIS; ANTIOXIDANT; RECEPTOR; PERMEABILITY; INFLAMMATION; FRACTALKINE; EXPRESSION; MELATONIN; Alpha-lipoic acid (ALA); Interstitial cystitis; Mast cell; Stress; Urinary bladder